Análisis del efecto económico financiero en las compañías de medicina prepagada por la aplicación de la nueva ley orgánica que regula las compañías que financien servicios de atención integral de salud prepagada y a las de seguros que oferten cobertura de seguros de asistencia médica en la ciudad de Quito. - Segovia Freire, Esthela Aurora (2017)
The objective of this paper is to analyze the economic and financial impact on prepaid medical companies by the application of the new organic regulates companies that finance comprehensive prepaid health care services and those that offer health insurance coverage In the city of Quito, by means of research carried out on 10 companies of prepaid medicine, the total population was taken to determine that the economic effect is unfavorable in the generation of profits, places of work, capital reserves, disbursements, coverage’s And outpatient medical care services in the event of catastrophic pre-existing diseases for companies, where the increase of rates is planned taking care of the economic condition of the client that does not affect the demand, companies are analyzing the evolution of the normative framework of the law To propose new strategies to enable it to Maintain its active position in the market and profit.